1980
DOI: 10.1063/1.439046
|View full text |Cite
|
Sign up to set email alerts
|

Observation of halos in rotationally inelastic scattering of Na2 from Ar

Abstract: We have measured level to level differential cross sections for rotational level changing collisions in ground state Na2 with Ar: Na2 (v\=0, ji=7)+Ar→Na2 (v\=0, jf)+Ar. Measurements range in Δj(jf−ji) from −4 to 80 and in Θ to π. A seeded supersonic beam source produces rotationally cold Na2 with a narrow velocity distribution; the levels are isolated and the differential cross sections are measured with cw dye lasers, using a new technique, angular distributions using the Doppler shift. The differential cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The singularity is caused by simultaneous zeros of B' and the square root in the denominator of (10a) both of which behave as lfx for x--*0. This feature of a rapid decrease of the cross section immediately beyond elastic scattering into the superelastic regime at all angles tends to be obscured by low resolving power in translation energy loss experiments, but is qualitatively confirmed by the observations of Pritchard and Kinsey [6] on the 7--.9 and 7--.3 rotational transitions of Ar-Na 2. In the inelastic regime u*<l, B>0, at increasing the other extrema B~: of B(XI) enter and leave the potentially contributing B range, see Fig.…”
Section: Ill Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The singularity is caused by simultaneous zeros of B' and the square root in the denominator of (10a) both of which behave as lfx for x--*0. This feature of a rapid decrease of the cross section immediately beyond elastic scattering into the superelastic regime at all angles tends to be obscured by low resolving power in translation energy loss experiments, but is qualitatively confirmed by the observations of Pritchard and Kinsey [6] on the 7--.9 and 7--.3 rotational transitions of Ar-Na 2. In the inelastic regime u*<l, B>0, at increasing the other extrema B~: of B(XI) enter and leave the potentially contributing B range, see Fig.…”
Section: Ill Discussionsupporting
confidence: 62%
“…A resolving power of about 5 % has been sufficient to resolve the structure of bulge scattering well, but, for non-hydrogenic molecules, is not enough to distinguish individual rotational transitions. Enormously more selective pump-and-probe laser techniques have also been used [4,6]. They are capable of labelling single j levels and, probing for f, resolve level-to-level transitions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work (15) indicated that the rotational-state distributions have a very weak dependence on ⌬v; one might reasonably expect to observe larger changes in the DCS, a more sensitive probe of the dynamics, for such large differences in the amount of energy transferred into vibration (recall that the energy of a quantum of D 2 vibration is approximately equal to the height of the reaction barrier on the minimum energy path), but this is not what we observe. Hints of this counterintuitive behavior were also found by Serri et al (24,25) when they measured DCSs for Na 2 ϩ Ar inelastic scattering and found that the peak scattering angle shifted by only 10°b etween ⌬v ϭ 0 and ⌬v ϭ 1 at large ⌬j. The vibrational spacing of Na 2 is small, and its interaction with Ar is almost totally repulsive.…”
Section: Sources Of Errormentioning
confidence: 75%
“…The most extensive diatomic data are probably those of Na 2 that include the entire rare gas series of collision partners. To bring emphasis to the generally unrecognized existence of common rotational distributions that occur in many diatomic systems, we display in Figure some of the Na 2 data 24 plotted in a form that reveals the close similarity of the rate constant distributions among the entire set of rare gas collision partners.
9 Rate constants for state-to-state rotational energy transfer from J = 4, J = 6 and J = 38 of A(Σ) Na 2 in collision with He, Ne, Ar, Kr, or Xe plotted against Δ J .
…”
Section: Discussionmentioning
confidence: 99%